2015
DOI: 10.1039/c5ra17137g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon degradation by a newly isolated thermophilic Anoxybacillus sp. with bioemulsifier production and new alkB genes

Abstract: In this work, a new thermophilic bacterial strain was isolated and identified as Anoxybacillus sp. WJ-4. This strain of WJ-4 can degrade a wide range of hydrocarbons, and production of an oligosaccharide–lipid–peptide bioemulsifier was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 54 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Several species of Geobacillus have recently been described as degraders of different hydrocarbons and may use a wide variety of hydrocarbons, especially crude oil, kerosene, and phenanthrene ( Marchant and Banat, 2010 ). Strains of Brevibacillus and Anoxybacillus have also been identified as hydrocarbon degraders under thermophilic conditions ( Xia et al, 2015 ), such as Brevibacillus sp. PDM-3, which degraded phenanthrene as a carbon source ( Reddy et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several species of Geobacillus have recently been described as degraders of different hydrocarbons and may use a wide variety of hydrocarbons, especially crude oil, kerosene, and phenanthrene ( Marchant and Banat, 2010 ). Strains of Brevibacillus and Anoxybacillus have also been identified as hydrocarbon degraders under thermophilic conditions ( Xia et al, 2015 ), such as Brevibacillus sp. PDM-3, which degraded phenanthrene as a carbon source ( Reddy et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the studies reported that Anoxybacillus sp. WJ-4 produced an oligosaccharide–lipid–peptide bioemulsifier with a high emulsification index of 60% ( Xia et al, 2015 ). A strain of Brevibacillus brevis isolated from an oil reservoir produced a lipopeptide-classified biosurfactant with an 80% emulsification index ( Mouafi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…and Anoxybacillus sp. such as Geobacillus caldoxylosilyticus (Marchant et al, 2002), Geobacillus kaustophilus TERI NSM (Sood and Lal, 2008), Geobacillus stearothermophilus KTCC-B7S (Sorkhoh et al, 1993), and Anoxybacillus rupiensis (Xia et al, 2015) were found to utilize various alkane hydrocarbons. Some geobacilli has been transferred to Parageobacillus genus (e.g., Parageobacillus caldoxylosilyticus) (Aliyu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…So far, there is only one reported study on genus Anoxybacillus on alkane hydroxylase involved in crude oil degradation as recorded by Anoxybacillus sp. WJ-4 [8]. Another study demonstrated that organic solvent tolerant Anoxybacillus sp.…”
Section: Growth and Enzyme Analysis Of Isolatesmentioning
confidence: 99%
“…The presence of complex compounds in crude oil such as alkanes, monocyclic, and polycyclic aromatic hydrocarbons causes toxicity to the environment and human health [2,4,5]. Crude oil biodegradation has been widely studied for the past few decades [6][7][8][9]. These studies have led to numerous microorganisms and their enzymes to be isolated and characterized.…”
Section: Introductionmentioning
confidence: 99%